2021
DOI: 10.1101/2021.07.20.21260565
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The devil is in the details: Reporting and transparent research practices in sports medicine and orthopedic clinical trials

Abstract: Introduction: While transparent reporting of clinical trials is essential to assess the risk of bias and translate research findings into clinical practice, earlier studies have shown that deficiencies are common. This study examined current clinical trial reporting and transparent research practices in sports medicine and orthopedics. Methods: The sample included clinical trials published in the top 25% of sports medicine and orthopedics journals over eight months. Two independent reviewers assessed pre-regi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…Approximately two thirds of papers did not contain enough information to determine whether observations were excluded without explanation [ 28 ]. A small exploratory analysis suggested that clinical trials that included flow charts were more likely to fully report attrition than studies that provided this information in the text [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately two thirds of papers did not contain enough information to determine whether observations were excluded without explanation [ 28 ]. A small exploratory analysis suggested that clinical trials that included flow charts were more likely to fully report attrition than studies that provided this information in the text [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study was pre-registered on the Open Science Framework (RRID:SCR_003238) and all generated data were made openly available. 22 Additional details regarding sample selection and screening, data abstraction, a sample size calculation and data for each included study can be found in the online supplemental materials .…”
Section: Methodsmentioning
confidence: 99%